1975
DOI: 10.1080/00071667508416174
|View full text |Cite
|
Sign up to set email alerts
|

Some observations on the caecal micro‐flora of the chick during the first two weeks of life

Abstract: 1. Changes in the caecal flora of chicks aged from approximately 3 h to 14 d were studied. 2. Counts obtained by means of a conventional anaerobic plating method and a method for the stricter anaerobes remained comparable throughout but occasionally it was found that strains of anaerobic bacteria isolated from the predominant flora of 4- to 14-d-old birds could not be grown when tested by the conventional method. 3. During the 14-d period approximately 100% of the organisms isolated on anaerobic plates utilise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
1

Year Published

1979
1979
2004
2004

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 19 publications
5
41
1
Order By: Relevance
“…Moreover, the inclusion of more than one strain of each type in most cases is thought to increase the chance of establishing at least one ofthe strains in different batches ofbirds which are given the protective treatment. Since the initial gut microflora of the young chick varies in composition and changes rapidly during the first few days of life (Mead & Adams, 1975), no account can be taken of the possible presence in the caeca of some of the bacterial types which are also included in the treatment mixture.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the inclusion of more than one strain of each type in most cases is thought to increase the chance of establishing at least one ofthe strains in different batches ofbirds which are given the protective treatment. Since the initial gut microflora of the young chick varies in composition and changes rapidly during the first few days of life (Mead & Adams, 1975), no account can be taken of the possible presence in the caeca of some of the bacterial types which are also included in the treatment mixture.…”
Section: Discussionmentioning
confidence: 99%
“…A number of the anaerobes, including some of the clostridia isolated were shown to utilize lactic acid as an energy source when tested by the methods of Barnes & Impey (1974 Mead & Adams (1975) showed that organisms, including faecal streptococci, which were capable of utilizing uric acid were present in high numbers immediately after hatching.…”
Section: Anti-salmonella Activity Of the Caecal Anaerobesmentioning
confidence: 99%
“…demonstrated that it was insufficient to try and establish a single VFA-producing anaerobe without at the same time establishing those organisms which will contribute towards lowering the pH of the caecum. The role of the lactobacilli which are not usually found in large numbers in the caeca until about the 2nd or 3rd day (Mead & Adams, 1975) remains to be investigated. Thus when Rantala & Nurmi (1973) prevent infection by Salmonella infantis by administering an anaerobic VL culture of organisms from the caeca of the adult bird they are probably speeding up the establishment of a mixture of organisms which will both lower the pH and produce the VFA's.…”
Section: Anti-salmonella Activity Of the Caecal Anaerobesmentioning
confidence: 99%
“…aviarius LU et al, 2003, DUMONCEAUX et al, 2006 1989B;KLOSE et al, 2006;ZHU, 2003;FUKATA et al, 1999B. gallinarum MEAD, 1989; , 1972;MEAD, 1975;LU et al, 2003;GONG et al, 2002;FUKATA et al, 1999GLUNDER, 1981 , 1989;LU et al, 2003;LAN et al, 2002;ZHU, 2003;GONG et al, 2002BANGERT et al, 1988MIKELSAAR, 1987MARTEAU, 2001E. faecalis X BARNES, 1972MEAD, 1975;BARNES, 1980E.…”
Section: Avestruzmentioning
confidence: 99%
“…gallinarum MEAD, 1989; , 1972;MEAD, 1975;LU et al, 2003;GONG et al, 2002;FUKATA et al, 1999GLUNDER, 1981 , 1989;LU et al, 2003;LAN et al, 2002;ZHU, 2003;GONG et al, 2002BANGERT et al, 1988MIKELSAAR, 1987MARTEAU, 2001E. faecalis X BARNES, 1972MEAD, 1975;BARNES, 1980E. faecium X BARNES, 1972LU et al, 2003;BARNES, 1980;KLOSE et al, 2006E.…”
Section: Avestruzmentioning
confidence: 99%